Recovery from Sepsis: Management beyond Acute Care - Andersen, Sarah K.; Herridge, Margaret S.; Fiest, Kirsten M. (Seminars in Respiratory and Critical Care Medicine, 2024)
Recovery from sepsis is a key global health issue, impacting 38 million sepsis survivors worldwide per year. Sepsis survivors face a wide range of physical, cognitive, and psychosocial sequelae. Readmissions to hospital following sepsis are an important driver of global healthcare utilization and cost. Family members of sepsis survivors also experience significant stressors related to their role as informal caregivers. Increasing recognition of the burdens of sepsis survivorship has led to the development of postsepsis recovery programs to better support survivors and their families, although optimal models of care remain uncertain. The goal of this article is to perform a narrative review of recovery from sepsis from the perspective of patients, families, and health systems.
Keywords: sepsis; critical care; postintensive care syndrome; recovery; patient-centered care; family-centered care; global health